Performance verification of the Abbott SARS-CoV-2 test for qualitative detection of IgG in Cali, Colombia. - Maria Del Mar Castro; Isabella Caicedo; Helen Johanna Ortiz-Rojas; Carmen Manuela Castillo; Adriana Giovanna Medina; Neal Alexander; Maria Adelaida Gómez; Ludwig L Albornoz (PLoS ONE)
Background Adequate testing is critically important for control of the SARS-CoV-2 pandemic. Antibody testing is an option for case management and epidemiologic studies, with high specificity and variable sensitivity. However, characteristics of local populations may affect performance of these tests. For this reason, the National Institute of Health (INS) and regulatory agencies in Colombia require verification of diagnostic accuracy of tests introduced to the Colombian market. Methods We conducted a validation study of the Abbott SARS-CoV-2 test for qualitative detection of IgG using the Abbott Architect i2000SR. Participants and retrospective samples were included from patients with suspected SARS-CoV-2 infection, age ≥18 years, and ≥8 days elapsed since initiation of symptoms. Pre-pandemic plasma samples (taken before October 2019) were used as controls. We estimated the sensitivity, specificity and agreement (kappa) of the Abbott IgG test compared to the gold standard (RT-PCR). Results The overall sensitivity was 83.1% (95% CI: 75.4-100). Sensitivity among patients with ≥14 days since the start of symptoms was 85.7%, reaching 88% in samples collected from patients with COVID-19 symptoms onset >60 days. Specificity was 100% and the kappa index of agreement was 0.804 (95% CI: 0.642-0.965). Conclusions Our findings show high sensitivity and specificity of the Abbott IgG test in a Colombian population, which meet the criteria set by the Colombian INS to aid in the diagnosis of COVID-19. Data from our patient groups also suggest that IgG response is detectable in a high proportion of individuals (88.1%) during the first two months following onset of symptoms.